Obesity and muscle‐macrophage crosstalk in humans and mice: A systematic review. (13th August 2019) - Rudrapatna, Srikesh; Bhatt, Meha; Wang, Kuan‐Wen; Bierbrier, Rachel; Wang, Pei‐Wen; Banfield, Laura; Elsheikh, Wagdi; Sims, E. Danielle; Peterson, Devin; Thabane, Lehana; Tarnopolsky, Mark A.; Steinberg, Gregory R.; et al.
Summary: Obesity is associated with the production of inflammatory cytokines that are implicated in insulin resistance (IR), and if not addressed, can lead to type 2 diabetes (T2D). The role of the immune system in skeletal muscle (SM) inflammation and insulin sensitivity is not yet well characterized. As SM IR is an important determinant of glycaemia, it is critical that the muscle‐immune phenotype is mapped to help design interventions to target T2D. This systematic review synthesized the evidence for SM macrophage content and phenotype in humans and murine models of obesity, and the association of muscle macrophage content and phenotype with IR. Results were synthesized narratively, as we were unable to conduct a meta‐analysis. We included 28 studies (n=10 human, n=18 murine), and all studies detected macrophage markers in SM. Macrophage content was positively associated with IR. In humans and mice, there was variability in muscle macrophage content and phenotype in obesity. Overall certainty in the evidence was low due to heterogeneity in detection methods and incompleteness of data reporting. Macrophages are detected in human and murine SM in obesity and a positive association between macrophage content and IR is noted; however, the standardization of markers, detection methods, and reporting of study details is warranted to accurately characterize macrophages and improve the potential for creating specific and targeted immune‐based therapies in obesity.